Amanah Saham National Berhad's (ASNB) promotional strategies and its relationship with customer motivation / Rabiatul Adawiyah Mohamad - Mohamad, Rabiatul Adawiyah (Faculty of Business and Management, 2008)
Every single company needs strategies in order to survive or to become a leader in the market nowadays, therefore a study towards findings the suitable strategies for Permodalan Nasional Berhad had been carried out. The purpose of the study are to determine the types of ASNB's promotional strategies, to identify the level of effectiveness promotional tools used by Amanah Saham Nasional Berhad (ASNS), to describe the correlations between ASNB's promotional strategies with customer motivation to invest and to examine the effect of the promotional tools with the customer motivation to invest in ASNB's products. A good research design will ensure that the marketing research project is conducted effectively. In this research, the exploratory, descriptive and causal effect has been used. The target sampling size for this study is 70 customers where the questionnaires were randomly distributed to those visiting ASNB service counter, Malacca Branch and 4 agents that are appointed by ASNB which are Maybank, CIMB, RHB and Pos Malaysia that also in Malacca. For this study, the non- probability sampling technique has been chosen. The non probability sampling method that will be used is convenience sampling. Moreover, computer programs have been developed to simplify and ease the research tabulation and analysis task. One of the most accurate and dependable statistical analysis packages is Statistical Package for Social Science (SPSS). Included in this package are the procedure of frequency, correlations analysis and regression analysis. The findings from the study found that several strategies should be recommended to Amanah Saham Nasional Berhad (ASNB). Firstly, ASNB should increase sales promotion such as high income distribution/dividend, offer scheme 'bantuan khairat kematian' to the investors, offer fixed and variable price as well as withdrawal or savings at any time for the investors as this can really encourage Bumiputera and non Bumiputera to invest in ASNB. Secondly, the information about PNB should be more advertise in television and newspaper since people are always see and read this two medium. The advertisement also should be more creative and attractive. Furthermore, PNB should hire more Sales Executives and Hire Individual Agents as the strategy to boost up ASNB's sales.